2003
DOI: 10.1097/00126097-200306000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of standard cuff on blood pressure readings in patients with obese arms. How frequent are arms of a ‘large circumference’?

Abstract: There is an overestimation of blood pressure when a standard cuff is used in obese subjects. The high prevalence of these individuals in our environment, both in the hypertensive and normotensive population, makes it necessary to have on hand different sizes of cuffs for taking blood pressure in order to avoid incorrect decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 12 publications
2
38
0
1
Order By: Relevance
“…Differences in blood pressure monitoring technique can result in significantly different readings. Numerous factors such as body position, arm position, inter-arm differences, cuff size, and cuff placement can affect the reading [3][4][5][6][7][8][9][10] . A study conducted recently on hypertensive patients compared usual blood pressure monitoring, ambulatory monitoring, and monitoring following the Canadian Hypertension Education Program protocol 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Differences in blood pressure monitoring technique can result in significantly different readings. Numerous factors such as body position, arm position, inter-arm differences, cuff size, and cuff placement can affect the reading [3][4][5][6][7][8][9][10] . A study conducted recently on hypertensive patients compared usual blood pressure monitoring, ambulatory monitoring, and monitoring following the Canadian Hypertension Education Program protocol 11 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2 studies, 11,13 cuff types were compared (standard vs large, rigid cylindrical vs conical); in 3 studies, 4,17,21 blood pressure measurements obtained via direct intra-arterial vs ausculatory/oscillometric techniques were compared; and in 6 studies, [14][15][16][18][19][20] blood pressure measurements obtained from the upper arm versus the forearm were compared.…”
Section: Resultsmentioning
confidence: 99%
“…Based on size and shape dimensions, an appropriately sized cuff as closely aligned to the AHA's guidelines as possible should be selected. This assessment is essential as evidence shows that standard cuffs yield overestimates of blood pressure in obese persons 13 compared with larger appropriately sized cuffs. Although the AHA recommends long cuffs with large arm circumferences and short upper arms, assessment and treatment of obese patients.…”
Section: Recommendations For Practicementioning
confidence: 99%
“…3 However, measurements of blood pressure in the forearm have been noted to vary by a mean of 7 to 15 mm Hg. 4 Fonseca-Reyes et al 2 reported that for each 5-cm increase in arm diameter, systolic blood pressure is overestimated by 2 to 5 mm Hg and diastolic blood pressure is overestimated by 1 to 3 mm Hg when a "standard" cuff is used on the patient's forearm. One question to be considered is how to determine what variance is clinically acceptable.…”
mentioning
confidence: 99%
“…2 As the arm circumference gets bigger, the bladder of the cuff must get longer and wider. The trouble with this standard, Currently, health care providers noninvasively measuring blood pressure in morbidly obese persons have 3 cuff choices: standard adult, large adult, and thigh.…”
mentioning
confidence: 99%